Vibration Response Analysis of Simply Supported Box Girder Bridge-Maglev Train in Accelerated Test of Changsha Maglev Express - Xiao Liang; Tianyong Jiang; Yue Hong; Jiabing Zhang; Mai Jiang; Zeyin Wang (Advances in Materials Science and Engineering)
In order to study and analyze the vibration response of simply supported box girder bridge-maglev vehicle, a 25 m span simply supported box girder bridge of Changsha Maglev Express was selected as the research object. Field tests were carried out to explore the dynamic response of maglev vehicle running on the bridge. Firstly, the dynamic characteristics of the bridge under the action of medium-low speed maglev train at different speeds were analyzed, and the vibration response of vehicle and bridge was studied at the design speed of 60∼130 km/h. Among them, the longitudinal acceleration of simply supported box girder ranged from 60 km/h to 130 km/h, which increased linearly with the speed of the train and reached the maximum 0.59 m/s2. Its longitudinal deflection also increased with the increase in train speed, which reached the maximum 1.605 mm at 130 km/h. When the speed is 130 km/h, the suspension gap of the maglev vehicle was concentrated in the range of 7.24∼11.50 mm. Through the test analysis, this study provides a basis for the vibration response analysis of simply supported box girder bridge-maglev train. It also provides a reference for the modification and formulation of relevant specifications and experimental verification for the acceleration work of medium-low speed maglev train in the future.